Réponses

2014-09-10T10:30:53+02:00
A=(3x+1)²+(3x+1)(5x-4)

(3x+1) (3x+1+5x-4)
(3x+1) (8x-3)

Soit 3x+1=0 d'où x=-1/3

ou 8x-3=0 d'où 8x=3 d'où x=3/8


Meilleure réponse !
2014-09-10T10:41:09+02:00
Bonjour

Soit A=(3x+1)²+(3x+1)(5x-4)

1 Développer et réduire A

A=(3x+1)²+(3x+1)(5x-4)
A = (9x²+6x+1) + (15x²-12x+5x-4)
A = 9x² + 6x + 1 + 15x² - 12x + 5x - 4
A = 9x² + 15x² + 6x + 5x -12x + 1 - 4
A = 24x² - x - 3

2 factoriser A

A=(3x+1)²+(3x+1)(5x-4)
A = (3x+1)(3x+1) + (3x+1)(5x-4)
A = (3x+1)[(3x+1)+(5x-4)]
A = (3x+1)(3x+1+5x-4)
A = (3x+1)(8x-3)

3 résoudre l'équation (3x+1)(8x-3) = 0

(3x+1)(8x-3) = 0
3x+1 = 0       ou     8x-3 = 0
    3x = -1                  8x = 3
      x = -1/3                 x = 3/8

S = {-1/3;3/8}